THE EFFECTIVENESS OF MAGGOT (Hermetia illucens) AS CATFISH FEED IN AQUAPONIC FARMING SYSTEMS - Sugiarto, Anton; Agustin, Heny (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2024)
The nutritional composition of maggots can be utilized as a substitute for pellets to reduce the cost of purchasing fish feed through an aquaponic system integrated with spinach plants. This study aimed to determine the effectiveness of maggots as catfish feed in an aquaponic farming system. The study was conducted from February to July 2021 at the Agroecotechnology Experimental Farm of Trilogy University, Jakarta. Meanwhile, maggot proximate testing was carried out at the Center for Agro Industry, Bogor, West Java. The experiment employed a one-factor Randomized Group Design (RAK) (catfish feed) with three levels: pellets (P0), maggot (P1), and a combination of pellets and maggot (P2). The results showed that using maggot as a substitute for catfish feed in the aquaponic system was considered effective because the weight and length of catfish harvested were as good as those fed with pellets. However, the growth of spinach plants integrated with catfish through the aquaponic system is still not optimal compared to conventional cultivation in general. Nevertheless, the growth results were still better than those integrated with catfish fed with pellet or combination feed. The spinach growth results indicated that the plant had a height of 18.20 cm, a total of 6.14 strands of leaves, a stem diameter of 2.25 mm, a root length of 35.51 cm, and a weight of 20.97 grams.